The Effect of Oxytocin Massage on Breast Milk Production in Postpartum Mothers at RSUD Dr. M. Thomsen Nias (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Insufficient breast milk production remains a leading cause of exclusive breastfeeding failure in postpartum mothers, particularly in the early postpartum period. Physiological and psychological barriers including impaired let-down reflexes, post-caesarean effects, and maternal anxiety reduce milk output and drive supplementation with infant formula. This study aimed to evaluate the effect of oxytocin massage on breast milk production in postpartum mothers admitted to RSUD dr. M. Thomsen Nias. A quantitative one-group pretest–posttest quasi-experimental design was employed. A total of 21 postpartum mothers were selected through purposive sampling from the Postnatal Ward of RSUD dr. M. Thomsen Nias from 1 to 14 February 2026. Oxytocin massage was administered along the spine to the 5th–6th costae for 10–15 minutes per session over three consecutive days. Breast milk volume was measured using a manual breast pump before and after each session. Data were analyzed using the Shapiro–Wilk normality test and the paired sample t-test. Mean breast milk production increased significantly from 22.86 ml (SD = 7.171) at pretest to 52.14 ml (SD = 16.013) at posttest, representing a 128.1% increase. The paired sample t-test confirmed a statistically significant effect (t = −8.476; df = 20; p = 0.000; p < α = 0.05). Oxytocin massage is an effective, safe, and easily implemented non-pharmacological intervention for enhancing breast milk production in postpartum mothers, with strong potential for integration into standard postnatal midwifery care protocols